Organizational behavior : human behavior at work - Newstrom, John W.; Davis, Keith, 1918-. (Boston, Mass : McGraw-Hill Companies, 1997)
"Great progress has been made in the field of organizational behavior since this book was first published. The study and practice known as organizational behavior goes beyond the integration and application of behavioral science to work situations. It is an emerging field in which many questions and opportunities for improvement remain. This book provides rich insights into people at work in all kinds of situations and organizations."
Rev. ed. of: Human behavior at work / Keith Davis, John W. Newstrom. 8th ed. 1989.
Includes bibliographical references and indexes.
English text.
Keywords: Organizational behavior; Industrial sociology